2021
DOI: 10.1021/acs.analchem.1c03884
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Wearable Sensors for Sensing Physiological Pressure Signals and β-Hydroxybutyrate in Physiological Fluids

Abstract: Flexible and wearable sensors have attracted much attention for their applications in health monitoring and the human–machine interaction. The most studied wearable sensors have been demonstrated for sensing a limited range of metabolites such as ions, glucose, uric acid, lactate, etc. Both sweat and urine contain numerous other physiologically relevant metabolites indicative of health and wellness. This work demonstrates the use of the wearable sensor for the detection of β-hydroxybutyrate (HB) in sweat. HB i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Channa et al also showed multiple applications of wearable devices during the pandemic, including preventing worsening of the disease, quarantine management, effective contact tracing, social or business interactions, smart learning/education, diagnosis of COVID-19, and stress management [S6]. Various researchers have proposed that physiological information obtained from integrated wearable devices, which have the utility of artificial intelligence (AI) and sensor fusion techniques, can have promising results, and are potentially ideal for the long-term monitoring of COVID-19 patients and other chronic diseases [ 8 ]. These are advantageous since the sensors are minimized and integrated into the network connectivity and predictive analytics to capture, transmit, and analyze biometric information automatically [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Channa et al also showed multiple applications of wearable devices during the pandemic, including preventing worsening of the disease, quarantine management, effective contact tracing, social or business interactions, smart learning/education, diagnosis of COVID-19, and stress management [S6]. Various researchers have proposed that physiological information obtained from integrated wearable devices, which have the utility of artificial intelligence (AI) and sensor fusion techniques, can have promising results, and are potentially ideal for the long-term monitoring of COVID-19 patients and other chronic diseases [ 8 ]. These are advantageous since the sensors are minimized and integrated into the network connectivity and predictive analytics to capture, transmit, and analyze biometric information automatically [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, an integrated wearable sensor was invented to monitor a progression of ketoacidosis using a βhydroxybutyrate biomarker as well as sensing physiological signals, such as vocal cord disorders and rhythm of the pulse beat as represented in Figure 5c. 88 With the another recent achievement, molecularly imprinted polymer-based artificial antibodies were exploited to monitor several metabolites, nutrient analytes, and amino acids associated with type 2 diabetes mellitus (T2DM), cardiovascular diseases (CVDs), and neurotransmitter activities. 75 Furthermore, a flexible microfluidic multiplexed immunosensor enabled monitoring of a panel of wound healing biomarkers, including transforming growth factor-α (TGF-α), interleukin-6 (IL-6), and IL-8.…”
Section: Need Of Multifunctional Sensing Technologies For Long-term C...mentioning
confidence: 99%
“…Portable sensors that provide cardiovascular health information are the remedy, and as such, their development has attracted much attention in recent years. 3 The latest research advances have shown their applications in sensing various health indicators such as temperature, 4 pressure signals, 5 glucose, 6 uric acid, 7 etc.…”
Section: ■ Introductionmentioning
confidence: 99%